Monika Sułkowska (red.) Frazeologia somatyczna w ćwiczeniach. - Grabowska, Monika; Ucherek, Witold (Neofilolog, 2021)
Katowice: Wydawnictwo Uniwersytetu Śląskiego, 2019, t. 1: A. Dolata-Zaród, D. Topa-Bryniarska, Język francuski, t. 2: A. Gwiazdowska, Z. Lamba, Język hiszpański, t. 3: L. Marcol-Cacoń, A. Pastucha-Blin, Język włoski.